Sistem Informasi Perpustakaan Online - Tri Sutrisna Number Wahid; Nina Marlina; Irwan Kurniawan; Sri Dianing Asri (JUST IT : Jurnal Sistem Informasi, Teknologi Informasi dan Komputer, 2021)
The library is a source of information, a source of research and recreation knowledge. Library as one of the information centers that are always dug up and developed. The library really helps the community, students for learning facilities and information centers. In its development the library in terms of data and documents stored in the form of data and information. The development of semi-modern libraries is to use a catalog (index) and the latest development is the emergence of digital libraries (digital libraries). Some libraries in schools still run a library management system with complicated records and report management. Therefore the use of a web-based library application system (digital library) in schools can save money and time because the process has been done by using a computer to minimize the loss of books, errors in making reports and reducing paper buildup. This research is intended to make it easier for librarians and can provide facilities for digital books bookmaking and book booking.Keywords : Library, School Library, Digital Library, Digital Books